2018
DOI: 10.1016/j.foodcont.2017.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for foodborne disease outbreaks in China, 2003 to 2008

Abstract: a b s t r a c tKnowledge of implicated food vehicles and contributing factors derived from foodborne disease outbreak (FBDO) investigations allows consumers to be educated on decreasing high-risk behavior to reduce the risk of being affected by foodborne diseases. Food safety regulatory authorities also need summary of outbreak data, as these data indicate where the existing food supply system should be improved. To obtain information on epidemiology of FBDOs in China, FBDOs reported to the China National Food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 21 publications
0
38
0
Order By: Relevance
“…Additionally, P. mirabilis has been associated with foodborne disease, despite their primary pathogenic role has not been confirmed [16][17][18], and may be a public health threat to society due to its strong association with a variety of human infectious diseases [19]. Therefore, more research is indicated to discuss and elucidate the zoonotic potential of P. mirabilis.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, P. mirabilis has been associated with foodborne disease, despite their primary pathogenic role has not been confirmed [16][17][18], and may be a public health threat to society due to its strong association with a variety of human infectious diseases [19]. Therefore, more research is indicated to discuss and elucidate the zoonotic potential of P. mirabilis.…”
Section: Introductionmentioning
confidence: 99%
“…Because human food and water sources can be easily contaminated by a broad spectrum of microbial pathogens, serious illness results if these microbial pathogens or their toxins are consumed [26]. Bacteria, viruses, and parasites are the most prevalent pathogens that cause foodborne diseases [27,28], but fungal foodborne diseases are also identified [29]. Bacteria are the most well-known foodborne pathogen, and cause the greatest number of foodborne illnesses, including the most hospitalizations (63.9%) and deaths (63.7%) [25].…”
Section: Foodborne Pathogensmentioning
confidence: 99%
“…During this period, leafy vegetables alone were estimated to be responsible for almost 2.2 million disease cases, or 22% of all foodborne disease cases, the most of any food commodity [ 60 ]. Similarly in China, plant commodities were associated with 48% (930) of foodborne disease outbreaks which occurred from 2003–2008 [ 61 ]. There are currently no published reports identifying the food vehicles for the transmission of foodborne disease in T&T. However, a survey of dietary consumption patterns in T&T revealed that 38% of participants regularly ate mixed raw vegetable salad, and a further 22% reported eating raw lettuce or tomatoes, thus the risk of consumption of contaminated produce is very apparent [ 62 ].…”
Section: Knowledge Gaps In Stec and Salmonella mentioning
confidence: 99%